EFEK PEMBERIAN DADIAH LINTAU SUMATERA BARAT TERHADAP PERUBAHAN STRUKTUR HISTOPATOLOGI PADA JARINGAN PANKREAS TIKUS MODEL DIABETES - Rinita Amelia; Rini Yulia; Putri Lisna; Anandia Putriyuni; Nadia Purnama D; Dessy Abdullah; Ade Teti Vani; Harnavi Harun (Yayasan Nusantara Hasana Berdikari, 2024)
Diabetes mellitus is a metabolic disorder characterized by the loss or progressive dysfunction of insulin-producing cells in the pancreas, leading to multiple long-term complications and organ damage. Dadiah is one of the traditional probiotic milk products in West Sumatra that is rich in lactic acid bacteria (BAL). Dadiah contains Lactobacillus fermentum which has characteristics as a probiotic and stimulates endogenous antioxidants. The study aimed to determine the difference in the effect of giving curd with dadiah probiotics (L. Fermentum) on changes in the structure of Langerhans pancreatic islets in streptozotocin-induced diabetes model rats. Methods This study was experimental with animals using 2 control groups and 3 intervention groups, namely the negative control was normal intervention mice, the positive control was diabetic mice without intervention. P1 in the 3g/300g BB intervention group, P2 in the low dose (L. Fermentum) probiotic intervention (7.1 × 1010 CFU/mL) and P3 in the high dose 2 probiotic intervention × 7.1 × 1010 CFU/mL)) each group consisted of 5 mice, the intervention lasted for 8 weeks, then organ sampling was carried out. The results of pancreatic histopathology and Langerhans islets showed that in the 3g/300g BB treatment of curd gave an overview of the best cell repair close to negative control (-)/normal Conclusion: Dadiah and probiotic have been pathologically proven to provide anatomical improvement to Langerhans islet cells that undergo degeneration and necrosis in diabetic model mice, due to the presence of antioxidant and probiotic activity. Therefore, dadiah and probiotic dadiah have proven to be useful as a supportive therapy for diabetics.